The Association Between ABO Blood Group and Preeclampsia: A Systematic Review and Meta-Analysis - Li, Ting; Wang, Yixiao; Wu, Lan; Ling, Zhonghui; Li, Chanjuan; Long, Wei; Xie, Kaipeng; Ding, Hongjuan (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective: This meta-analysis comprehensively evaluated the association between ABO blood group and the risk of PE. Design: Systematic review and meta-analysis. Data sources: PubMed, Web of Science and ScienceDirect databases from their inception to September 23, 2020. Methods: Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were obtained through random-effects and fixed-effects models according to heterogeneity. Meta-regression analysis was applied to explore the source of heterogeneity. We conducted a subgroup analysis by the publication year, study design, sample size, state, NOS score, mild or severe PE, and early-onset or late-onset PE. Additionally, we calculated the rate of each ABO blood group in PE by total pooled effects. Results: A total of 12 articles with 714,153 patients were included in our analysis. Compared to the control group, the O blood group presented a lower risk of PE (OR 0.95, 95% CI 0.93-0.97). The A blood group and AB blood group presented a higher risk (ORA 1.03, 95% CIA 1.01-1.05). However, the total pooled OR and 95% CI for the B blood group were not significant (OR 1.02, 95% CI 0.98-1.05). The funnel plot and linear regression equation showed that there was no publication bias for the O, A or B blood groups (all P > 0.05). However, the funnel plot and linear regression equation for the AB blood group were obviously asymmetric (P < 0.05), and the publication bias persisted even after the trim-and-fill method was applied (I2 67.8%, P < 0.05). Meta-regression analysis did not find a specific source of heterogeneity. The subgroup analysis results were generally consistent with the pooled results. The A blood group showed a greater correlation with early-onset PE, and the other blood groups showed no significant differences (OR 0.53, 95% CI 0.33-0.83). In PE, the rates of the O, A, B, and AB blood group decreased gradually (0.39, 0.33, 0.19, 0.07). Conclusion: These findings can be used to alert obstetricians to the need for early detection of PE in women with A and AB blood groups, enabling them to provide timely and effective interventions. Systematic review registration: Prospero CRD42021227930.